Promosi Ulos Ragi Hotang dalam Meningkatkan Daya Tarik Wisatawan di Desa Meat Kabupaten Toba - Ana Setya Sibagariang; Roida Lumbantobing; Hanna Dewi Aritonang; Mery Silalahi; Ade Putera Arif Panjaitan (Universitas Katolik Widya Karya Malang, 2023)
The aim of this research is to determine the description and impact of promotion of Ulos Ragi Hotang on increasing tourist attraction in Meat Village, Toba Regency, because promotion is a very important thing to do in increasing tourist attraction. Mazid stated that promotion is a marketing activity to introduce, inform and offer a destination to the wider public so they want to come to visit. The method used in this research is qualitative with a descriptive approach, with 10 research subjects selected to collect data in the field. The results of this research show that the promotions that have been carried out by the government and the community through face-to-face sales (personal selling), publicity (Publicity), sales promotions, namely an increase in the attraction of tourists to come to visit the Meat Village, although not too much. However, there are changes from the previous year. In connection with the research results, the author provides input for the community government, Pokdarwis to maximize the promotion of Ulos Ragi Hotang in a sustainable manner, not just by activities carried out in the meat village such as the Meat art festival and the thousand tent activity as an annual event, but the government provides encouragement, especially to the community. weaving craftsmen to be more effective in promoting, then the community must maintain the beauty of the motifs and continue to preserve the culture of Ulos Ragi Hotang weaving as a superior product from Meat village